Pengaruh Pelatihan, Lingkungan Kerja Fisik, dan Budaya Organisasi Terhadap Kinerja Karyawan Pada Perusahaan Daerah Air Minum Lumajang - Miftahul Ulum; Ema Desia Prajitiasari; Eka Bambang Gusminto (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
The study aims to know and analyze the influence of training, physical work environment, and organizational culture toward employee on Lumajang Water Supply Company. This research is called explanatory research. Population is all regular employees on Lumajang Water Supply Company with amount 61 respondents and sample selected by jenuh sampling or sensus method with amount 61 respondents. Data analyze method is multiple liniear regression. The result of study shows up that Training of employees on Lumajang Water Supply Company significantly affect employees performance with positive relationship, Physical Work Environment on Lumajang Water Supply Company significantly affect employees performance with positive relationship, and Organizational Culture on Lumajang Water Supply Company significantly affect employees performance with positive relationship. This indicates that the Training, Physical Work Environment, and Organizational Culture can improve Performance of employees on Lumajang Water Supply Company optimally. Keywords: Organizational culture, Performance, Physical work environment, Training